2013
DOI: 10.1039/c3ay40841h
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nucleosides and nucleobases in Isatidis Radix by HILIC-UPLC-MS/MS

Abstract: To establish an ultra-high performance liquid chromatography coupled with triple quadrupole mass (HILIC-UPLC-MS/MS) for determination of sixteen nucleosides and nucleobases in Isatidis Radix. Chromatographic separation was carried out on a Acquity UPLC BEH Amide column with gradient elution of acetonitrile (containing 0.1% acetic acid) and water (containing 0.8% acetic acid and 10 mmol L À1 ammonium acetate) at a flow rate of 0.3 mL min À1 , the column temperature was set at 35 C; Waters XevoÔ TQ worked in mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Nucleosides, nucleotides, and nucleobases, a group of highly active compounds, are involved in the regulation and modulation of various physiological processes in human body . As shown in Table , various natural product samples, including functional foods , medicinal plants , medicine and food dual purpose products , are containing nucleosides‐based compounds. It is clear that UAE is the common sample preparation method for compound extraction, and due to the high sensitivity and wide linear dynamic range for quantification, triple quadrupole MS (TQ‐MS) is frequently used for detection.…”
Section: Applications Of Hilic In Natural Products Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleosides, nucleotides, and nucleobases, a group of highly active compounds, are involved in the regulation and modulation of various physiological processes in human body . As shown in Table , various natural product samples, including functional foods , medicinal plants , medicine and food dual purpose products , are containing nucleosides‐based compounds. It is clear that UAE is the common sample preparation method for compound extraction, and due to the high sensitivity and wide linear dynamic range for quantification, triple quadrupole MS (TQ‐MS) is frequently used for detection.…”
Section: Applications Of Hilic In Natural Products Analysismentioning
confidence: 99%
“…Taking advantage of the rapid and excellent separation performance of HILIC–ESI‐TQ‐MS/MS, nucleosides, and nucleobases in medicinal plants Cordyceps and Radix Isatidis were also analyzed. After optimization and validation, the developed method was applied for the analysis of real samples that were collected from different locations in China.…”
Section: Applications Of Hilic In Natural Products Analysismentioning
confidence: 99%
“…In our previous research, it was found that the nucleosides were difficult to obtain good separation in high proportion of organic solvents because of their high and similar polarity. 5 So the proportion of organic phase slowly increased from 3 to 10% in 12 min. As shown in Figure 3, the nucleosides were completely separated with good peak symmetry.…”
Section: Optimization Of Hplc Conditionsmentioning
confidence: 99%
“…16 Many analytical methods including high performance liquid chromatography (HPLC), 17,18 capillary zone electrophoresis (CZE) 19 and ultra-high performance liquid chromatography coupled with triple quadrupole mass have been developed for the determination of one of the three chemical types bioactive compounds (alkaloids, nucleosides and phenylpropanoids) in Radix Isatidis or its pharmaceutical dosage forms. 5,20 However, to the best of our knowledge, no method has been developed for simultaneous analysis of alkaloids, phenylpropanoids, nucleosides in Radix Isatidis or its relevant pharmaceutical dosage forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation